1992
DOI: 10.1073/pnas.89.12.5670
|View full text |Cite
|
Sign up to set email alerts
|

Coherent 25- to 35-Hz oscillations in the sensorimotor cortex of awake behaving monkeys.

Abstract: Synchronous 25-to 35-Hz were observed in local field potentials and unit activ in sensorimotor cortex of awake rhesus monkeys. The osatory epiode occurred often when the monkeys retrieved raisins from a KIliver board or from unseen locations uin somatosenor feedback; they occurred less often during perfnce of repetitive wrist flexion and extension movements. The amplitude, duration, and frequency of oscillations were not directly related to movement prameters In behaviors studied so far. The occurrence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
506
3
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 897 publications
(555 citation statements)
references
References 19 publications
39
506
3
7
Order By: Relevance
“…We conclude that, at least in the present experimental paradigm, the spatial extent of the beta band modulations does not colocalize with the fMRI effects of the interaction analysis (Simon et al, 2002). The reason for this discrepancy could be due to the type of responsiveness of the beta rhythm to sensory stimuli: beta range oscillations are widely observed in the sensorimotor cortex in relation to motor behaviors in both humans ( Salmelin and Hari, 1994;Pfurtscheller and Lopes da Silva, 1999;Brovelli et al, 2002;Salenius and Hari, 2003) and nonhuman primates (Rougeul et al, 1979;Murthy and Fetz, 1992;Sanes and Donoghue, 1993;MacKay and Mendonca, 1995;Brovelli et al, 2004). In particular, power suppression in the beta band, known as event-related desynchronization (ERD), has been observed during tasks activating the sensorimotor cortex using both EEG (Pfurtscheller, 1981) and electrocorticographic (ECoG) techniques (Arroyo et al, 1993;Toro et al, 1994, Crone et al, 1998a.…”
Section: Erps and Seeg In The Beta Frequency Do Not Colocalize With Tmentioning
confidence: 56%
“…We conclude that, at least in the present experimental paradigm, the spatial extent of the beta band modulations does not colocalize with the fMRI effects of the interaction analysis (Simon et al, 2002). The reason for this discrepancy could be due to the type of responsiveness of the beta rhythm to sensory stimuli: beta range oscillations are widely observed in the sensorimotor cortex in relation to motor behaviors in both humans ( Salmelin and Hari, 1994;Pfurtscheller and Lopes da Silva, 1999;Brovelli et al, 2002;Salenius and Hari, 2003) and nonhuman primates (Rougeul et al, 1979;Murthy and Fetz, 1992;Sanes and Donoghue, 1993;MacKay and Mendonca, 1995;Brovelli et al, 2004). In particular, power suppression in the beta band, known as event-related desynchronization (ERD), has been observed during tasks activating the sensorimotor cortex using both EEG (Pfurtscheller, 1981) and electrocorticographic (ECoG) techniques (Arroyo et al, 1993;Toro et al, 1994, Crone et al, 1998a.…”
Section: Erps and Seeg In The Beta Frequency Do Not Colocalize With Tmentioning
confidence: 56%
“…More recently, cortical inhibitory networks have also been proposed to play a critical role in the generation of faster activities that include oscillations in the low (i.e, beta-gamma oscillations at 20-80 Hz) and high frequency range (>80 Hz, so called ripples) (Buzsáki et al, 1992). Interestingly, both beta-gamma rhythms and ripples occurring in cortical areas (Gray et al, 1989;Murthy and Fetz, 1992;Singer and Gray, 1995), including those of the limbic system Chrobak and Buzsáki, 1998;Csicsvari et al, 1999Csicsvari et al, , 2003, have been implicated in higher brain processes such as attention, sensorimotor integration, consciousness, learning and memory (Girardeau et al, 2009;Montgomery and Buzsáki, 2007). Therefore, it has been suggested that these oscillatory rhythms represent the basic neuronal processing state of the brain (Basar et al, 1999).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%
“…In the hippocampus, at least two distinct gamma generators have been identified: one depends on the perforant path input from the entorhinal cortex, whereas the other emerges in the CA3 region Csicsvari et al, 2003). Cortical neurons are phase-locked to the local gamma oscillation (Gray et al, 1989;Murthy and Fetz, 1992;Steriade et al, 1996;Csicsvari et al, 2003), which allows them to synchronize within a narrow temporal window. This phase-locking is brought about by volleys of inhibitory currents produced by local interneurons (Buzsáki et al, 1983;Csicsvari et al, 2003;Bragin et al, 1995a;Hasenstaub et al, 2005).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%